Understanding the Burden: Oral Health Impact Profile in Oral Lichen Planus with and Without Systemic Diseases – A Cross-Sectional Study - Palak J. Choudhary; Preeti P. Nair; Devashree Shukla; Annette M. Bhambal; Anshika Khare; Roopali Patel (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Oral health-related quality of life (OHRQoL) is vital to overall well-being. Oral lichen planus (OLP), a benign immune-mediated disorder, causes chronic inflammation and often leads to significant yet undiagnosed burdens such as depression, systemic illnesses, and reduced quality of life. Objectives: This study compared oral health impact profile (OHIP) scores in OLP patients in the presence and absence of systemic illnesses to evaluate the effect of illness severity on OHRQoL. Methods: This hospital-based cross-sectional study included 252 adults (≥18 years) with clinically and histopathologically confirmed OLP, selected through simple random sampling. Exclusion criteria were other oral lesions, pregnancy, tobacco use, and poor communication. Systemic conditions (hypertension, diabetes, thyroid disorders) were identified via biochemical tests and prescriptions. OHRQoL was assessed using OHIP-14, and data were analyzed using SPSS 26 with t-tests at 5% significance. Results: The mean age of patients was 45.7 years, with a predominance of females. Systemic illnesses notably worsened OHRQoL, especially in physical pain, psychological discomfort, and handicap dimensions. Gender had no significant effect, as both female and male patients exhibited comparable OHRQoL scores. Conclusion: OLP reduces OHRQoL, which is deteriorated by systemic diseases. A holistic management approach is essential to enhance the overall well-being in affected patients.